Strategies to Mitigate Climate Change and Carbon Pollution - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
ncreasing global warming associated with continuous emission of greenhouse gases (GHGs, mainly CO2) and abiotic stresses such as drought, salinity have direct impact on the productivity of trees and shrubs and crops. This is aggravated with deforestation, illegal logging, expansion of agriculture and urbanization leading to climate change across the globe. This situation is of great concern to adopt strategy to mitigate climate change and carbon load from the atmosphere. In view of the facts that trees have capacity to capture solar radiation and CO2 from the atmosphere leading to the production of timber and biomass, thereby reducing atmospheric temperature. Therefore, the plantation of trees and reforestaton is considered a viable strategy to mitigate climate change and carbon pollution. Recently Paris Climate Change summit has recommended to reduce 2 °C globally. Different countries have given emphasis to implement this strategy. FAO Newsletter has recommended the cultivation of tress and transplantation to mitigate climate change and carbon pollution. Plants have capacity to capture solar radiation during the process of photosynthesis, thereby reducing atmospheric temperature.